(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this investigation, we used the coolant fluid, which is represented by MEPCM in MPFHS, with fins (square, triangular, and circular). Also, the Nusselt number, Reynolds numbers, and pressure drop are investigated. The MEPCM suspension uses microcapsules made from PCM (RT44) and shell materials (PAO). These capsules are immersed in pure fluids (pure oil, pure water, and ethylene glycol) at concentrations ranging from 0–20%. The results obtained reveal that MPFHS uses of MEPCM suspensions as a coolant fluid give better performance. Nessult number increased with increasing Reynolds number for all pure fluid based (RT44+PAO) suspension. Also, the variations in performance with Reynolds number for pure oil based (RT44+PAO) suspension at concentration 2%, give high performance. Because of materials properties used (RT44 and PAO), where (RT44) having a higher latent heat of fusion and PAO having a higher thermal conductivity. Furthermore, circular fins give high performance compared to square and triangular fins. Also, unfinned heat sinks give high performance compared with other types of fins due to lower pressure drop and high heat transfer coefficient.